Chronic Lung Disease of Early Infancy. - Bland, Richard D., 1940- (Informa Healthcare, 1999)
Presents the clinical and pathological features of bronchopulmonary dysplasia, a disease that accounts for the majority of long-term hospitalizations, slow growth and recurrent early childhood respiratory ailments that are common in low-birth-weight newborns.